Adaptive PID-like fault-tolerant control for robot manipulators with given performance specifications. Issue 3 (3rd March 2020) - Cao, Ye; Song, Yong-Duan
ABSTRACT: This paper investigates the trajectory tracking problem of rigid robot manipulators with unknown dynamics and actuator failures. The goal is to achieve desirable tracking performance with a simple and low-cost control strategy. By introducing a new form of parameter estimation error, together with an error transformation, a robust adaptive and fault-tolerant control scheme is developed without the need for fault information nor precise robotic mathematical model. It is shown that, with the proposed control, the tracking error is ensured to converge to an adjustable residual set within prescribed finite time at a user pre-assignable decay rate. The appealing feature of the developed control also lies in its simplicity in structure (i.e. PID form) and effectiveness in dealing with modelling uncertainties as well as actuation faults.